High prevalence of psychiatric comorbidities in children and adolescents at a tertiary epilepsy center - Maria Antonia Serra-Pinheiro; Isabella D'andrea-Meira; Abraão Iuri Medeiros Angelim; Fernanda Alves Fonseca; Nicolle Zimmermann (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Epilepsy is highly comorbid with psychiatric disorders and a significant amount of the morbidity related to epilepsy is in fact a result of psychiatric comorbidities. Objective: To investigate the frequency of different psychiatric comorbidities in children with refractory epilepsy. Methods: We present preliminary observational data from a series of patients (n=82) examined in the psychiatric branch of a tertiary epilepsy center in Rio de Janeiro, Brazil. Patients were classified as presenting autism spectrum disorders, mood disorders, anxiety disorders, disruptive disorders, attention deficit hyperactivity disorder (ADHD), intellectual development disorder, psychotic episode, dissociative/conversive disorders or others. We determined the frequency of each disorder, along with demographic data, medications prescribed, electroencephalogram findings and additional medical examinations and consultations. Results: The most common comorbidities in our sample were autism spectrum disorders and ADHD. Antipsychotics and selective serotonin uptake inhibitors were the most commonly prescribed psychiatric medications. Conclusions: Knowledge about the prevalence of such comorbidities may provide more targeted interventions in Psychiatry and Psychology services linked to epilepsy centers.